2005
DOI: 10.1016/j.ejvs.2004.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Apoptosis in Primary Varicose Veins

Abstract: Apoptosis is down regulated in the medial layer of varicose veins. This dysregulation of the cellular mechanism that maintains normal tissue integrity is mediated through the intrinsic apoptotic pathway and may be among the causes of primary varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 50 publications
(58 reference statements)
3
25
0
2
Order By: Relevance
“…It has been demonstrated immunohistochemically that the expression of bax and caspase 9 is significantly reduced in SMCs from varicose compared with non-varicose veins. The expression of caspase 8 and Fas in SMCs, however, does not differ significantly between varicose and non-varicose veins 90,91 . Therefore, the intrinsic rather than the extrinsic pathway seems dysregulated in varicose veins as bax and caspase 9 are involved in the former, whereas caspase 8 and Fas are involved in the latter 90,91 (Fig.…”
Section: Smooth Muscle Cell Proliferation and Migrationmentioning
confidence: 80%
See 2 more Smart Citations
“…It has been demonstrated immunohistochemically that the expression of bax and caspase 9 is significantly reduced in SMCs from varicose compared with non-varicose veins. The expression of caspase 8 and Fas in SMCs, however, does not differ significantly between varicose and non-varicose veins 90,91 . Therefore, the intrinsic rather than the extrinsic pathway seems dysregulated in varicose veins as bax and caspase 9 are involved in the former, whereas caspase 8 and Fas are involved in the latter 90,91 (Fig.…”
Section: Smooth Muscle Cell Proliferation and Migrationmentioning
confidence: 80%
“…hypoxia, mechanical stretch and low shear stress) Endothelial injury and leucocyte activation (inflammation) 90 . Improperly regulated apoptosis may contribute to pathological conditions involving faulty DNA repair mechanisms and cell cycle disruption.…”
Section: Smooth Muscle Cell Proliferation and Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has demonstrated that MGP regulated apoptosis at different stages of cell differentiation [57]. Decreased apoptosis in the medial layer of varicose veins has been described [59, 60]. Involvement of MGP in the decreased programmed varicose cell death will require further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, they presented healthy increase of collagen fibers and decrease in density and size of elastic fibers. The immunoreactivity to caspase-9 and Bax in muscular layer cells was significantly smaller in varicose veins when compared to healthy ones, demonstrating a low apoptotic regulation [11]. Beside these concepts about chronic varicose veins, one well carried out study showed that two-minute distensions of 300mmHg in intact human saphenous veins induced p38 activation, which is associated with apoptosis [6].…”
Section: -Representative Photomicrographs Of Immunohistochemical Analmentioning
confidence: 99%